How Efficient Are Clear Aligners? Clear Aligners vs Traditional Orthodontic Treatment: A Systematic Review - Yasemin Bahar Acar; Ayşegül Kovan; Mustafa Ates; Sibel Biren (Galenos Yayinevi, 2014)
Purpose:The purpose of the present review is to update knowledge of the literature and better understand the efficiency and abilities of clear aligners and to clarify their indications for use.Materials and Method:The study question was defined as ''How efficient is orthodontic treatment with clear aligners in comparison to fixed orthodontic treatment in patients with permanent dentition?'' An Internet-based search was performed with 6 databases: Medline, PubMed, Clinical Key, ProQuest Dissertations and Theses, Dentistry and Oral Sciences Source (EBSCO Host), and the Cochrane Library. The final search was run in January 2014. Key words used were clear aligner, eCligner, Invisalign, and AsoAligner.Results:We retrieved 110 publications from the databases. After reviewing titles and abstracts, case reports and clinical studies reporting treatment outcomes on segmental dental arches (i.e., anterior dentition) were excluded. Finally, 3 studies that addressed the study question were included in the review.Conclusion:Not enough studies were available to arrive at definite conclusions to compare clear aligner and fixed orthodontic treatment. In simpler cases, Invisalign may result in treatment outcomes as good as those of traditional orthodontic treatment. However, controlled clinical studies are necessary to define and support the abilities and limits of clear aligner therapy with evidence.